TFLAT ANDROID-BASED FOR PRONUNCIATION PRACTICE CLASS: STUDENTS AND LECTURERS’ PERCEPTIONS - Halim, Abd; Masriadi; Dahnair, Dahniar; Taufik, Muhammad; Halim, Nur Mutmainna (Elite : English and Literature Journal, 2024)
This study aims to examine the perception of using the TFlat English Pronunciation application and determine how students and instructors view the app, its influence on language learning, and its possible advantages. The research used E-Learning theory adapted from Akaslan and Law (2010) and employed qualitative methods to explore diverse user experiences. To find out the perceptions of informants (10 students and 1 lecturer), the researchers interviewed them to investigate more about the usefulness of this application. The findings revealed that students found TFlat to be a valuable application for improving their English pronunciation in E-learning. They appreciated the user-friendly features and accessibility of TFlat, which enhanced their overall E-learning experience. The lecturer also acknowledged the benefits of TFlat in improving students’ pronunciation skills and promoting accessibility. However, they suggested addressing compatibility issues with iPhones and expanding the app’s features for more extensive practice in future utilization. Overall, the study highlighted the importance of practical technological tools like TFlat in modern education and emphasized the need for exercise diversification and broader accessibility across devices.